Error analysis in answering system of of linear equations with two variables questions based on Newman indicator - Mita Akbar Sukmarini; Hermanto Hermanto (Universitas Islam Negeri Maulana Malik Ibrahim, 2021)
This study focuses on the forms of errors made by students in solving math problems, especially on the material of a two-variable system of linear equations. The purpose of this research is describing detail the form of errors made by students based on error indicators according to the Newman Stages. The data collection technique used is observation. By collecting data in the form of written test results from students, the forms of errors made by students were obtained, including: at stage (1) the form of the error was wrong in writing down known information, incomplete in writing down the information contained in the question, and wrong in determining the information in question, at stage (2) it is not appropriate to write a mathematical model from known information, and does not use variable symbols to simplify calculations, at stage (3) does not operate similar variables, substitutes wrong values, does not apply rules of operation, miscalculations, and did not get the final result of the calculation process, at stage (4) did not change the variable symbol into the form that the question asked, did not provide information on the final answer, and wrote conclusions but did not match what the questions asked.